A comparative study on the effect of tin precursor concentration on the tin(IV) oxide nanoparticles growth and the photocatalysis properties / Shahida Ismail and Vicinisvarri Inderan - Ismail, Shahida; Inderan, Vicinisvarri (2020)
The studies of SnO2 in photocatalysis application are still limited and are not widely investigated. Improvement in the fundamental knowledge of SnO2 as photocatalyst as well as its structural and morphology was done through further studies of the SnO2 characterization. Nanostructured of SnO2 can be schemed by controlling the parameters that affecting the morphology of the materials. There are several parameters like temperature, pH, concentration, and duration of hydrothermal process that can influence the structure and morphology of SnO2. Therefore, an investigation on the effect of tin precursor concentration on the tin(IV) oxide nanoparticles was carried out. The characterization data of as-synthesized SnO2 used in this study were determined using hydrothermal method before proceeding to the analysis. Based on FESEM analysis, the morphology of tin oxide from cluster of irregular shape at 0.08 M developed to nanorods structured at 0.2 M as the precursor concentration increases. Based on the data analysis tin(IV) oxide prepared with 0.12 M shows well formation of dimensional nanostructure. The best selected sample (0.12 M) was tested on Methylene Blue dye (6 ppm) for photocatalytic degradation. The data analysis shows that 15 minutes is required to achieve 84.75 % degradation and 105 minutes for 100 % degradation of methylene blue. At optimum concentration , the well-ordered of the structured increase the surface area, hence the active sites increase for catalytic rection to occur. Thus, the concentration of tin precursor can affect the morphology of the tin(IV) oxide and also the photocatalysis performance.